Improvement of Warehouse Operations Management by Considering Competencies of Human Resources. (2017) - Palšaitis, Ramūnas; Čižiūnienė, Kristina; Vaičiūtė, Kristina
Abstract: Clients generally require logistics services package from organizations engaged in the provision of warehouse logistics services. Successful performance of employees in organizations depend on their ability to adapt to changing environment, where personal competence is an essential factor. The article examines peculiarities of human resources impacts and its employment as a tool to develop organizations providing warehouse logistics services and ensure the quality of such services. The conducted qualitative research enabled to identify problem aspects of human resources, i.e. warehouse employees and managers, and competencies in logistics organizations